Globalization and migration: A "unified brain drain" model - Elise S. Brezis; Ariel Soueri (Bar-Ilan University, Department of Economics, 2012)
Globalization has led to a vast flow of migration of workers but also of students. The purpose of this paper is to analyze the migration of individuals encompassing decisions already at the level of education. We develop a unified brain drain model that incorporates the decisions of an individual vis - à - vis both education and migration. In the empirical part, this paper addresses international flows of migration within the EU and presents strong evidence of concentration of students in countries with high - quality education. This phenomenon, as the usual brain drain, has two opposite effects on social mobility.
Keywords: F22; I23; J24; 330; Brain drain; Globalization; Higher education; Human capital; Migration; Mobility; Bologna process; Globalisierung; Brain Drain; Hochschulreform; Internationale Wanderung; Studierende; EU-Staaten